2019
DOI: 10.1371/journal.pone.0215130
|View full text |Cite
|
Sign up to set email alerts
|

"Smart Eye Camera": An innovative technique to evaluate tear film breakup time in a murine dry eye disease model

Abstract: Tear film breakup time (TFBUT) is an essential parameter used to diagnose dry eye disease (DED). However, a robust method for examining TFBUT in murine models has yet to be established. We invented an innovative device, namely, the "Smart Eye Camera", which addresses several problems associated with existing methods and is capable of evaluating TFBUT in a murine DED model. We compared images taken by existing devices and the Smart Eye Camera in a graft-versus-host disease-related DED murine model. We observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 21 publications
1
48
0
Order By: Relevance
“…The SEC may have the following potential advantages in healthcare: (1) It could be applied to other ophthalmological diseases, particularly in the anterior segment of the eye. We previously reported that this device could evaluate tear film breakup time and corneal epithelial disorder in a dry eye disease mouse model [ 8 ]. The size of the mouse eye is about 3-mm wide [ 17 ] and is much smaller than that in humans.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The SEC may have the following potential advantages in healthcare: (1) It could be applied to other ophthalmological diseases, particularly in the anterior segment of the eye. We previously reported that this device could evaluate tear film breakup time and corneal epithelial disorder in a dry eye disease mouse model [ 8 ]. The size of the mouse eye is about 3-mm wide [ 17 ] and is much smaller than that in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Although the non-specialists can use this portable slit-lamp device, the ophthalmologists may need to evaluate the recorded images to make a cataract diagnosis. SEC is a smartphone attachment that allows video recording [ 8 ], and thus, it may be useful in telemedicine. Several studies have demonstrated that ophthalmological diagnoses are amenable to remote medicine, as the diagnosis is made based on images of the eye [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SEC has a function that converts the light source from the smartphone into a 1-mm thin beam, allowing it to fall on the crystalline lens. Moreover, the SEC has a convex lens that magnifies the reflected light to a degree sufficient for ocular diagnosis [ 5 , 15 , 16 ]. The iPhone 7, 8, or SE (Apple Inc., Cupertino, CA, USA) was used to record the ocular video.…”
Section: Methodsmentioning
confidence: 99%
“…The SEC converts the light of the smartphone to the essential light needed for the ophthalmological diagnosis. We previously demonstrated its diagnostic function for cataracts in humans and the dry eye disease mouse model [ 5 , 15 , 16 ]. However, no study has investigated the ACD evaluation and angle estimation function of the portable and recordable slit-lamp device.…”
Section: Introductionmentioning
confidence: 99%